Changes in Vascular Tone Occur Early During Hemodialysis Treatments Independently of Volume Reduction. Issue 7 (23rd October 2015) - Power, Albert; Charitaki, Evangelia; Davenport, Andrew
Abstract: Hypotension commonly occurs during hemodialysis (HD). Hypotension can result from an absolute reduction in plasma volume following excessive ultrafiltration or from a reduction in vascular tone. We hypothesized that changes in vascular tone could occur during dialysis. Aortic pulse wave velocity (aPWV) was measured in 197 HD patients, mean age 63.3 ± 16.6 years, 62% male, 49% diabetic, during a single HD session. aPWV did not change (9.6 ± 2.2 vs. 9.6 ± 2.2 m/s) with HD. Systolic blood pressure (SBP) declined from 151 ± 31 to 147 ± 32 after 20 min and to 140 ± 36 mm Hg on completion of HD ( P < 0.05), with an ultrafiltration volume of 2.2 ± 0.9 L over a 3.9 ± 0.4 h HD session. Aortic SBP declined from 154 ± 32 to 146 ± 29 after 20 min and 143 ± 35 at the end of HD, P < 0.001. Aortic augmentation index (Aortic Aix) decreased from 65% (52–79%) to 36.7% (23.3–52.9%) by 20 min and to 34.3 (15.1–49.1%) on completion of HD ( P < 0.05), and brachial augmentation index (brachial Aix) from 5.7% (−25.2 to 27.5%) to −1.9% (−2.2 to 30.1%) and −6.6% (−44 to 22.7%), respectively, P < 0.05. Diastolic reflection area (DRA) increased from 36.7 (27.9–46.3) to 40.4 (32.2–51) after 20 min and 47.1 (34.2–60.5) on completion of HD, P < 0.05. We report changes in arterial tone within 20 min of starting HD, when minimal ultrafiltration has occurred, suggesting that volume changes may not be the only predisposing cause of intradialytic hypotension. The combination of a fall in SBP and a rise in DRA would suggest a reduction in coronary blood flow in keeping with reports of "myocardial stunning" during HD.